Service Desk in Perspective of Information Technology Infrastructure Library 3rd-Version - Dimas Mahardika; Tawar; Saima Ahmed Rahin; Franklin Ore Areche; Ari Fajar Santoso; Ahmad Suryan (Engineering Science Letter, 2022)
ICT services are an essential element in modern organizations. Understanding the workings of service systems with specific frameworks helps manage services well. One of the services in this management is the Service Desk or Helpdesk. This study aims to explain the Service Desk using the ITIL V.3 framework. The method used is descriptive qualitative using relevant references. The results of this study indicate that ITIL V.3 can be used to describe the management of the Service Desk accurately.